Eksklusivisme Penganut Sampradaya Hare Krishna di Desa Sibanggede (1999-2022) - Ni Nyoman Tri Elisia Merayanti; I Nyoman Wijaya (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the exclusivism of Hare Krishna Sampradaya followers at Radha Rasesvara Ashram, Sibanggede Village, Abiansemal District, Badung Regency during the period 1999-2022. The background of this research is the phenomenon of exclusivism or self-isolating behavior practiced by Hare Krishna followers following the issuance of the Joint Decree of PHDI and MDA Bali Number: 106/PHDI-Bali/XII/2020 and Number: 07/SK/MDA-Prov Bali/XII/2020 concerning restrictions on the propagation of non-Balinese dresta sampradaya teachings. This study aims to analyze the background of followers joining the Hare Krishna sampradaya, identify the causes of exclusivist attitudes, and examine their implications for the surrounding community. The research employs historical method encompassing heuristics, source criticism, interpretation, and historiography using Max Weber's Rational Instrumental Action theory. Data collection was conducted through in-depth interviews with Hare Krishna followers, ashram managers, and local residents, as well as literature review of relevant documents and publications. The findings reveal that followers joined Hare Krishna due to interest in spiritual books and the teachings conveyed. The exclusivism emerged as a defensive response to hate speech, threats of ashram closure, and persecution experienced by one member. This self-isolating attitude manifested through reduced public activities, stricter visitor regulations, and the avoidance of religious attributes in public spaces. The implication of this exclusivism is decreased social interaction between followers and the surrounding community, although neighborly relations continue normatively.